A 23 years audit of packed red blood cell consumption in a university hospital in a developing country. Issue 3 (December 2015) - Abdel Gader, Abdel Galil M.; AlGhumlas, Abeer K.; Al Momen, Abdul Karim M.; Badri, Motasim
Abstract: Background: There is paucity of information on the blood transfusion practice in developing countries. The current audit aims to find out the long term trend in the consumption of packed red blood cells (PRBCs) in a large Saudi teaching hospital in Riyadh Materials and methods: We analyzed the annual consumption of PRBCs from 1985 to 2007 in seven major hospital divisions (Medicine, General Surgery, Pediatrics, Obstetrics and Gynecology, Cardiac Surgery, Accident and Emergency and Renal Dialysis Unit) at the 850-bed King Khalid University Hospital (KKUH), Riyadh. Results: Grand total consumption of PRBCs was 345, 642 units. The consumption increased gradually and peaked in the year 1994, dropped to 30.4% 6 years later and then increased gradually thereafter, due to the expansion in the number of patients cared for in the Departments of Medicine, Cardiac Surgery and Accident and Emergency, while in the Department of Pediatrics the drop in consumption continued unabated. In the Renal Dialysis Unit consumption was minimal with the use of erythropoietin therapy. The crossmatch:transfusion ratio uncovered gross over-ordering of PRBCs and wastage of blood bank resources in most hospital divisions most notably in the Department of Obstetrics and Gynecology. Conclusion: The results obtained indicate clearly that there has been overuse of blood products that dropped markedly in years coinciding with the worldwide apprehension about the safety of transfusion therapy particularly HIV transmission. This factor in addition to the current implementation of strict guidelines is gradually improving transfusion practices in our institute.